A controllable degradable polyethylene material and preparation method thereof
By blending the microcapsule degradation agent with polyethylene and using twin screw extrusion granulation technology, the contradiction between the degradation performance and service life of polyethylene materials is solved, controllable degradation and high temperature stability are achieved, cost is reduced, and application prospects are expanded.
Patent Information
- Application Number
- CN202411980979.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
There is a contradiction between the degradation performance and service life of existing biodegradable polyethylene materials, and it has high cost, low mechanical strength and poor temperature resistance.
The microcapsule degradation agent is blended with polyethylene and the controllable degradation polyethylene material is prepared by double screw extrusion granulation. The microcapsule degrading agent consists of a core layer, a shell layer I and a shell layer II, which provides support, and a shell layer II is polylactic acid and can withstand high temperatures.
The controllable degradation of polyethylene materials is achieved, ensuring the thermal processing performance and service life of the material, while reducing costs and improving application prospects.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer modified materials and relates to a controllably degradable polyethylene material and a preparation method thereof. Background Art
[0002] In order to deal with white pollution, biodegradable materials such as PLA and PBAT are being vigorously promoted and applied in packaging, film and other fields. However, these biodegradable packaging materials have problems such as high price, low mechanical strength and poor temperature resistance.
[0003] PE has excellent performance and low price. It was once commonly used in the field of packaging and film, but it is difficult to degrade. Although studies have shown that PE can be degraded by microorganisms such as Aspergillus niger after being fully photothermally aged by catalysts to form oligomers with active groups, the addition of large amounts of such polyolefin photothermal aging catalysts will lead to a significant decrease in the product's service life and thermal processing performance. Although catalysts with weak catalytic degradation capabilities can guarantee service life, they will lead to incomplete catalytic degradation and easy generation of microplastics. For the contradiction between polyolefin degradation performance and service life, the prior art has not disclosed an effective solution.
[0004] Patent CN118005849A involves degradable polyethylene, but this patent is achieved by directly adding a degradation agent and does not involve controlled sustained-release degradation by encapsulating the degradation agent in microcapsules.
[0005] Patent CN113136069A relates to a degradable film, but the claim is that the degradability of the product is improved by adding a fast degrader to the raw materials and controlling the ratio between LDPE, LLDPE, HDPE and the fast degrader. It does not involve controlled sustained-release degradation of microcapsules.
[0006] Therefore, it is of great significance to study a controllable degradable polyethylene material and its preparation method. Summary of the invention
[0007] The purpose of the present invention is to solve the problems existing in the prior art and to provide a controllably degradable polyethylene material and a preparation method thereof.
[0008] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing a controllable degradable polyethylene material, comprising: blending a microcapsule degradation agent with polyethylene and subjecting the mixture to twin-screw extrusion granulation to obtain the controllable degradable polyethylene material;
[0010] The preparation steps of microcapsule degradation agent are as follows:
[0011] Acetic acid, a polyolefin degradation agent, nano-titanium dioxide and chitosan are added into water to obtain a mixed solution A, and then the mixed solution A is stirred at a stirring rate of 600 to 1500 r / min while the temperature is raised from room temperature to 40 to 80° C. to slowly evaporate water until the water is evaporated to dryness, and in the process of evaporating water, a glutaraldehyde solution is added dropwise at a rate of 0.05 to 0.0625 ml / h to precipitate chitosan to solidify titanium dioxide and adhere to the surface of the polyolefin degradation agent, thereby obtaining a product A;
[0012] The dosage ratio of acetic acid, polyolefin degradation agent, nano titanium dioxide, chitosan, water and glutaraldehyde solution is 2-3 ml: 2-3 g: 0.12-0.36 g: 2-6 g: 200-300 ml: 0.5 ml, acetic acid is one of the solvents of chitosan; the content of glutaraldehyde in the glutaraldehyde solution is 25-75 wt%;
[0013] The polylactic acid and the product A are added into dichloromethane to obtain a mixed solution B, and then the mixed solution B is stirred at a stirring rate of 1500 to 3000 r / min while the temperature is raised from room temperature to 40 to 50° C. to evaporate the dichloromethane so that the polylactic acid is precipitated and wraps the product A, thereby preparing a microcapsule degradation agent;
[0014] Wherein, the usage ratio of polylactic acid, product A and dichloromethane is 1-2g:1g:50-200ml;
[0015] Under the above two stirring rates and the ratio of each substance, the particle size of the microcapsule degradation agent of the present application can be controlled to be in the range of 10 to 50 μm, and the structure of the prepared microcapsule degradation agent is ensured to be intact; if the particle size is too large, greater than 50 μm, it is difficult to ensure the integrity of the microcapsules in the subsequent twin-screw extrusion, and once the microcapsules are damaged, the degradation agent will cause serious thermal degradation of the material during the thermal processing process; if the particle size is too small and the shell is too thin, it is also easy to be damaged;
[0016] The particle size of the microcapsule degradation agent is 10 to 50 μm;
[0017] After the microcapsule degradation agent is blended with polyethylene and granulated by twin-screw extrusion, the structural integrity rate of the microcapsule degradation agent is greater than 90%.
[0018] As the preferred technical solution:
[0019] In the preparation method as described above, the processing temperature of the twin screw is 150-160° C., which is lower than the temperature of PLA.
[0020] In the preparation method as described above, in step (1), acetic acid, a polyolefin degradation agent, nano-titanium dioxide and chitosan are added to water, and stirred at a stirring rate of 600 to 1500 r / min to obtain a mixed solution A, and the stirring time is 1 to 2 hours.
[0021] According to the preparation method described above, the precipitation time of chitosan is 8 to 10 hours.
[0022] According to the preparation method described above, the precipitation time of polylactic acid is 3 to 5 hours.
[0023] According to the preparation method described above, the particle size of nano titanium dioxide is 10 to 40 nm.
[0024] According to the preparation method described above, the viscosity of chitosan is ≥200 mPa·s.
[0025] The present invention also provides a controllable degradable polyethylene material prepared by the preparation method as described in any one of the above items, the controllable degradable polyethylene material comprises a microcapsule degradation agent and polyethylene; the microcapsule degradation agent comprises a core layer, a shell layer I and a shell layer II; the shell layer I wraps the core layer, and the shell layer II wraps the shell layer I; the core layer is a degradation agent for polyolefins; after the core layer is wrapped by the shell layer I and the shell layer II, PE can be prevented from contacting the microcapsule degradation agent; the shell layer I is a mixture of nano titanium dioxide and chitosan, and the shell layer I serves as a skeleton inner layer, and after wrapping the core layer, it provides support for the core layer to ensure the processing integrity of the microcapsule; the shell layer II is polylactic acid, and the high melting point of polylactic acid enables it to withstand the thermal processing temperature of PE, so even if a degradation agent with a strong degradation effect on PE is used, the thermal processing performance and service life of PE can be guaranteed.
[0026] Beneficial effects:
[0027] (1) The microcapsule degradation agent of the present invention has a double-layer shell structure. The shell layer I provides support to ensure the processing integrity of the microcapsule degradation agent. The polylactic acid is used as the shell layer II to enable it to withstand the thermal processing temperature of PE. Finally, the prepared microcapsule degradation agent can ensure the thermal processing performance and service life of PE even if a degradation agent with a strong degradation effect on PE is used.
[0028] (2) After the controllably degradable polyethylene material prepared by the present invention is discarded in the natural environment, the polyolefin degradation agent will gradually degrade the PE to form low-molecular polymers with active groups as the shell layer I and shell layer II disintegrate, ultimately achieving controllable degradation.
[0029] (3) The controllably degradable polyethylene material prepared by the present invention can reduce environmental pressure and has a lower price than PLA and PBAT, and has broad application prospects. DETAILED DESCRIPTION
[0030] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0031] In order to ensure that the properties of the materials used in each embodiment and comparative example are fully disclosed, the manufacturers and brands of the materials are indicated, and products of other manufacturers and brands that meet the requirements of the present invention are also feasible.
[0032] The testing methods of the relevant performance indicators in the following embodiments and comparative examples are as follows:
[0033] Degradation rate: The degradable polyethylene materials prepared in each embodiment and comparative example were used as samples, and were buried on the soil surface under controlled composting degradation conditions of 65% humidity and 37°C under daily lighting environment. A blank control group containing no samples was set up, and the carbon dioxide emissions after 90 days and 180 days of degradation were collected and calculated, and the mass loss rate of the samples was calculated. The degradation rates after 90 days and 180 days of degradation were calculated based on the carbon dioxide emissions.
[0034] A method for preparing a controllable degradable polyethylene material, comprising the following steps:
[0035] (1) Acetic acid, a polyolefin degradation agent, nano-titanium dioxide (particle size of 10-40 nm) and chitosan (viscosity ≥ 200 mPa·s) were added to water, and the mixture was stirred at a stirring rate of 600-1500 r / min for 1-2 h to obtain a mixed solution A. The mixed solution A was then stirred at a stirring rate of 600-1500 r / min while the temperature was raised to 40-80° C. to evaporate water until the water was evaporated to dryness. During the evaporation of water, 0.05-0.0625 ml / h, so that chitosan precipitates solidified titanium dioxide and adheres to the surface of the polyolefin degradation agent, thereby obtaining product A; wherein the amount ratio of acetic acid, polyolefin degradation agent, nano-titanium dioxide, chitosan, water and glutaraldehyde solution is 2-3ml:2-3g:0.12-0.36g:2-6g:200-300ml:0.5ml, the content of glutaraldehyde in the glutaraldehyde solution is 25-75wt%, and the precipitation time of chitosan is 8-10h;
[0036] (2) adding polylactic acid and the product A obtained in step (1) into dichloromethane to obtain a mixed solution B, and then stirring the mixed solution B at a stirring rate of 1500 to 3000 r / min while raising the temperature to 40 to 50° C. to evaporate the dichloromethane so that the polylactic acid precipitates and wraps the product A, thereby obtaining a microcapsule degradation agent; wherein the amount ratio of the polylactic acid, the product A and the dichloromethane is 1 to 2 g: 1 g: 50 to 200 ml, and the precipitation time of the polylactic acid is 3 to 5 h;
[0037] The particle size of the prepared microcapsule degradation agent is 10 to 50 μm;
[0038] (3) The microcapsule degradation agent obtained in step (2) is blended with polyethylene and then subjected to twin-screw extrusion granulation to obtain a controllably degradable polyethylene material; wherein the processing temperature of the twin-screw is 150-160° C., and the mass ratio of the microcapsule degradation agent to the polyethylene is 3-8:100.
[0039] The finally prepared controllable degradable polyethylene material comprises a microcapsule degradation agent and polyethylene;
[0040] The microcapsule degradation agent comprises a core layer, a shell layer I and a shell layer II, wherein the shell layer I wraps the core layer, and the shell layer II wraps the shell layer I, the core layer is a degradation agent for polyolefins; the shell layer I is a mixture of nano titanium dioxide and chitosan; and the shell layer II is polylactic acid;
[0041] After the microcapsule degradation agent is blended with polyethylene and granulated by twin-screw extrusion, the structural integrity rate of the microcapsule degradation agent is greater than 90%;
[0042] The service life of the controllable degradable polyethylene material is greater than 400 hours in an oven aging time at 150°C; the degradation rate of the controllable degradable polyethylene material after 90 days of degradation is greater than 80%, and the degradation rate after 180 days of degradation is greater than 98%.
[0043] Example 1
[0044] A method for preparing a controllable degradable polyethylene material, comprising the following steps:
[0045] (1) Acetic acid, a polyolefin degradation agent (manufacturer: Liaoning Jinke Plastic Technology Co., Ltd., brand: Jinke Baiwokai, model: Bio-CDJ-PE degradation agent), nano-titanium dioxide (particle size: 10-40 nm) and chitosan (viscosity: 300 mPa·s) were added to water, and stirred at a stirring rate of 1500 r / min for 1.5 h to obtain a mixed solution A. The mixed solution A was then stirred at a stirring rate of 1500 r / min while the temperature was raised to 60°C. Evaporating water until it is dried, and in the process of evaporating water, adding glutaraldehyde solution at a rate of 0.056 ml / h, so that chitosan precipitates solidified titanium dioxide and adheres to the surface of the polyolefin degradation agent, thereby preparing product A; wherein the amount ratio of acetic acid, polyolefin degradation agent, nano-titanium dioxide, chitosan, water and glutaraldehyde solution is 3 ml:3 g:0.36 g:6 g:300 ml:0.5 ml, the content of glutaraldehyde in the glutaraldehyde solution is 25 wt%, and the precipitation time of chitosan is 9 hours;
[0046] (2) adding polylactic acid (manufacturer: Anhui Fengyuan Biotechnology Co., Ltd., brand: FY801) and the product A obtained in step (1) into dichloromethane to obtain a mixed solution B, and then stirring the mixed solution B at a stirring rate of 3000 r / min while raising the temperature to 45°C to evaporate the dichloromethane so that the polylactic acid precipitates and wraps the product A, thereby obtaining a microcapsule degradation agent; wherein the amount ratio of the polylactic acid, the product A and the dichloromethane is 2g:1g:150ml, and the precipitation time of the polylactic acid is 4h;
[0047] The average particle size of the prepared microcapsule degradation agent is 30 μm;
[0048] (3) The microcapsule degradation agent obtained in step (2) is blended with polyethylene (manufacturer: LyondellBasell Industries, brand: NA324013) and then subjected to twin-screw extrusion granulation to obtain a controllably degradable polyethylene material; wherein the processing temperature of the twin-screw is 160° C., and the mass ratio of the microcapsule degradation agent to the polyethylene is 3:100.
[0049] The finally prepared controllable degradable polyethylene material comprises a microcapsule degradation agent and polyethylene;
[0050] The microcapsule degradation agent comprises a core layer, a shell layer I and a shell layer II, wherein the shell layer I wraps the core layer, and the shell layer II wraps the shell layer I, the core layer is a degradation agent for polyolefins; the shell layer I is a mixture of nano titanium dioxide and chitosan; and the shell layer II is polylactic acid;
[0051] After the microcapsule degradation agent was blended with polyethylene and granulated by twin-screw extrusion, the structural integrity rate of the microcapsule degradation agent was 93%;
[0052] The service life of the controllable degradable polyethylene material is 510 hours after aging in an oven at 150°C; the degradation rate of the controllable degradable polyethylene material is 87% after 90 days of degradation, and the degradation rate is 99% after 180 days of degradation.
[0053] Comparative Example 1
[0054] A method for preparing a degradable polyethylene material, which is basically the same as that in Example 1, except that: step (1) is not performed, the product A in step (2) is replaced by the polyolefin degradation agent of Example 1 (the amount used is equal to the mass of the polyolefin degradation agent of Example 1), and the particle size of the microcapsule degradation agent is controlled to be the same as that in Example 1;
[0055] The structure of the finally obtained degradable polyethylene material is basically the same as that of Example 1, except that: the microcapsule degradation agent has only a core layer and a shell layer composed of polylactic acid; the thickness of the shell layer composed of polylactic acid is equal to the sum of the thickness of the shell layer I and the shell layer II in Example 1;
[0056] After the microcapsule degradation agent is blended with polyethylene and granulated by twin-screw extrusion, the structural integrity rate of the microcapsule degradation agent is 40%;
[0057] The service life of the degradable polyethylene material is 80h in an oven aging time at 150℃;
[0058] By comparing Comparative Example 1 with Example 1, it can be seen that the service life of the degradable polyethylene material prepared in Comparative Example 1 is greatly reduced. This is because the shell strength of the microcapsule degradation agent in Comparative Example 1 is insufficient, which will cause the shell to rupture during screw extrusion, thereby reducing the structural integrity of the microcapsule degradation agent after extrusion granulation. Due to the rupture of the shell, the polyolefin degradation agent will come into contact with PE during the thermal processing, resulting in serious thermal degradation problems that make the degradation uncontrollable, ultimately resulting in a greatly reduced service life of the degradable polyethylene material.
[0059] Comparative Example 2
[0060] A method for preparing a degradable polyethylene material is basically the same as that of Example 1, except that the nano-titanium dioxide in step (1) is omitted.
[0061] The structure of the finally obtained degradable polyethylene material is basically the same as that of Example 1, except that: the shell layer I is chitosan;
[0062] After the microcapsule degradation agent was blended with polyethylene and granulated by twin-screw extrusion, the structural integrity rate of the microcapsule degradation agent was 52%;
[0063] The service life of the biodegradable polyethylene material is 105h after aging in an oven at 150℃.
[0064] By comparing Comparative Example 2 with Example 1, it can be seen that the service life of the microcapsule degradation agent prepared in Comparative Example 2 is greatly reduced. This is because the shell layer I of the microcapsule degradation agent prepared in Comparative Example 2 lacks the reinforcement of titanium dioxide, resulting in insufficient strength of the microcapsule shell layer, which will cause the shell layer to rupture during screw extrusion, thereby reducing the structural integrity of the microcapsule degradation agent after extrusion granulation. Due to the rupture of the shell layer, the shell layer of the microcapsule degradation agent will rupture during the thermal processing process and release the polyolefin degradation agent, so that the polyolefin degradation agent contacts PE in advance, resulting in serious thermal degradation and uncontrollable degradation, and ultimately causing the service life of the degradable polyethylene material to be greatly reduced.
[0065] Example 2
[0066] A method for preparing a controllable degradable polyethylene material, comprising the following steps:
[0067] (1) Acetic acid, a polyolefin degradation agent (manufacturer: Liaoning Jinke Plastic Technology Co., Ltd., brand: Jinke Baiwokai, model: Bio-CDJ-PE degradation agent), nano-titanium dioxide (particle size: 10-40 nm) and chitosan (viscosity: 250 mPa·s) were added to water, and stirred at a stirring rate of 1000 r / min for 1.5 h to obtain a mixed solution A. Then, the mixed solution A was stirred at a stirring rate of 1000 r / min while the temperature was raised to 60°C. Evaporating water until it is dried, and in the process of evaporating water, adding glutaraldehyde solution at a rate of 0.056 ml / h, so that chitosan precipitates solidified titanium dioxide and adheres to the surface of the polyolefin degradation agent, thereby preparing product A; wherein the amount ratio of acetic acid, polyolefin degradation agent, nano-titanium dioxide, chitosan, water and glutaraldehyde solution is 2ml:2g:0.24g:4g:250ml:0.5ml, the content of glutaraldehyde in the glutaraldehyde solution is 25wt%, and the precipitation time of chitosan is 9h;
[0068] (2) adding polylactic acid (manufacturer: Anhui Fengyuan Biotechnology Co., Ltd., brand: FY801) and the product A obtained in step (1) into dichloromethane to obtain a mixed solution B, and then stirring the mixed solution B at a stirring rate of 2400 r / min while raising the temperature to 45° C. to evaporate the dichloromethane so that the polylactic acid precipitates and encapsulates the product A, thereby obtaining a microcapsule degradation agent; wherein the amount ratio of the polylactic acid, the product A and the dichloromethane is 1 g:1 g:100 ml, and the precipitation time of the polylactic acid is 4 h;
[0069] The average particle size of the prepared microcapsule degradation agent is 25 μm;
[0070] (3) The microcapsule degradation agent obtained in step (2) is blended with polyethylene (manufacturer: LyondellBasell Industries, brand: NA324013) and then subjected to twin-screw extrusion granulation to obtain a controllably degradable polyethylene material; wherein the processing temperature of the twin-screw is 160° C., and the mass ratio of the microcapsule degradation agent to the polyethylene is 5:100.
[0071] The finally prepared controllable degradable polyethylene material comprises a microcapsule degradation agent and polyethylene;
[0072] The microcapsule degradation agent comprises a core layer, a shell layer I and a shell layer II, wherein the shell layer I wraps the core layer, and the shell layer II wraps the shell layer I, the core layer is a degradation agent for polyolefins; the shell layer I is a mixture of nano titanium dioxide and chitosan; and the shell layer II is polylactic acid;
[0073] After the microcapsule degradation agent was blended with polyethylene and granulated by twin-screw extrusion, the structural integrity rate of the microcapsule degradation agent was 96%;
[0074] The service life of the controllable degradable polyethylene material is 540 hours after aging in an oven at 150°C; the degradation rate of the controllable degradable polyethylene material is 85% after 90 days of degradation, and the degradation rate is 99% after 180 days of degradation.
[0075] Example 3
[0076] A method for preparing a controllable degradable polyethylene material, comprising the following steps:
[0077] (1) Acetic acid, a polyolefin degradation agent (manufacturer: Liaoning Jinke Plastic Technology Co., Ltd., brand: Jinke Baiwokai, model: Bio-CDJ-PE degradation agent), nano-titanium dioxide (particle size: 10-40 nm) and chitosan (viscosity: 200 mPa·s) were added to water, and stirred at a stirring rate of 600 r / min for 1.5 h to obtain a mixed solution A. The mixed solution A was then stirred at a stirring rate of 600 r / min while the temperature was raised to 60°C for evaporation. The method comprises the steps of: heating the mixture until the water is evaporated to dryness, and in the process of evaporating the water, adding a glutaraldehyde solution dropwise at a rate of 0.056 ml / h, so that the chitosan precipitates and solidifies the titanium dioxide and adheres to the surface of the polyolefin degradation agent, thereby obtaining a product A; wherein the amount ratio of acetic acid, the polyolefin degradation agent, nano-titanium dioxide, chitosan, water and the glutaraldehyde solution is 2 ml: 2 g: 0.12 g: 2 g: 200 ml: 0.5 ml, the content of glutaraldehyde in the glutaraldehyde solution is 25 wt %, and the precipitation time of the chitosan is 9 h;
[0078] (2) adding polylactic acid (manufacturer: Anhui Fengyuan Biotechnology Co., Ltd., brand: FY801) and the product A obtained in step (1) into dichloromethane to obtain a mixed solution B, and then stirring the mixed solution B at a stirring rate of 1500 r / min while raising the temperature to 45°C to evaporate the dichloromethane so that the polylactic acid precipitates and encapsulates the product A, thereby obtaining a microcapsule degradation agent; wherein the amount ratio of the polylactic acid, the product A and the dichloromethane is 1g:1g:50ml, and the precipitation time of the polylactic acid is 4h;
[0079] The average particle size of the prepared microcapsule degradation agent is 40 μm;
[0080] (3) The microcapsule degradation agent obtained in step (2) is blended with polyethylene (manufacturer: LyondellBasell Industries, brand: NA324013) and then subjected to twin-screw extrusion granulation to obtain a controllably degradable polyethylene material; wherein the processing temperature of the twin-screw is 160° C., and the mass ratio of the microcapsule degradation agent to the polyethylene is 8:100.
[0081] The finally prepared controllable degradable polyethylene material comprises a microcapsule degradation agent and polyethylene;
[0082] The microcapsule degradation agent comprises a core layer, a shell layer I and a shell layer II, wherein the shell layer I wraps the core layer, and the shell layer II wraps the shell layer I, the core layer is a degradation agent for polyolefins; the shell layer I is a mixture of nano titanium dioxide and chitosan; and the shell layer II is polylactic acid;
[0083] After the microcapsule degradation agent was blended with polyethylene and granulated by twin-screw extrusion, the structural integrity rate of the microcapsule degradation agent was 92%;
[0084] The service life of the controllable degradable polyethylene material is 530 hours after aging in an oven at 150°C; the degradation rate of the controllable degradable polyethylene material is 83% after 90 days of degradation, and the degradation rate is 99% after 180 days of degradation.
Claims
1. A method for preparing a controllable degradable polyethylene material, characterized in that: The microcapsule degradation agent is mixed with polyethylene and then subjected to twin-screw extrusion granulation to obtain a controllably degradable polyethylene material; The preparation steps of microcapsule degradation agent are as follows: (1) adding acetic acid, a polyolefin degradation agent, nano-titanium dioxide and chitosan into water to obtain a mixed solution A, then stirring the mixed solution A at a stirring rate of 600 to 1500 r / min while raising the temperature to 40 to 80° C. to evaporate water until the water is evaporated to dryness, and in the process of evaporating water, adding glutaraldehyde solution at a rate of 0.05 to 0.0625 ml / h, so that chitosan precipitates and solidifies titanium dioxide and adheres to the surface of the polyolefin degradation agent, thereby obtaining a product A; The dosage ratio of acetic acid, polyolefin degradation agent, nano titanium dioxide, chitosan, water and glutaraldehyde solution is 2-3 ml: 2-3 g: 0.12-0.36 g: 2-6 g: 200-300 ml: 0.5 ml; the content of glutaraldehyde in the glutaraldehyde solution is 25-75 wt %; (2) adding polylactic acid and product A into dichloromethane to obtain a mixed solution B, and then stirring the mixed solution B at a stirring rate of 1500 to 3000 r / min while raising the temperature to 40 to 50° C. to evaporate the dichloromethane so that the polylactic acid precipitates and wraps the product A, thereby preparing a microcapsule degradation agent; Wherein, the usage ratio of polylactic acid, product A and dichloromethane is 1-2g:1g:50-200ml; The particle size of the microcapsule degradation agent is 10 to 50 μm; After the microcapsule degradation agent is blended with polyethylene and granulated by twin-screw extrusion, the structural integrity rate of the microcapsule degradation agent is greater than 90%.
2. The preparation method according to claim 1, characterized in that: The processing temperature of the twin screw is 150-160°C.
3. The preparation method according to claim 1, characterized in that: In step (1), acetic acid, a polyolefin degradation agent, nano-titanium dioxide and chitosan are added to water, and stirred at a stirring rate of 600 to 1500 r / min to obtain a mixed solution A, and the stirring time is 1 to 2 hours.
4. The preparation method according to claim 1, characterized in that: The precipitation time of chitosan is 8 to 10 hours.
5. The preparation method according to claim 1, characterized in that: The precipitation time of polylactic acid is 3 to 5 hours.
6. The preparation method according to claim 1, characterized in that: The particle size of nano titanium dioxide is 10 to 40 nm.
7. The preparation method according to claim 1, characterized in that: The viscosity of chitosan is ≥200mPa·s.
8. The controllably degradable polyethylene material obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The controllable degradable polyethylene material includes a microcapsule degradation agent and polyethylene; the microcapsule degradation agent includes a core layer, a shell layer I and a shell layer II; the shell layer I wraps the core layer, and the shell layer II wraps the shell layer I; the core layer is a degradation agent for polyolefins; the shell layer I is a mixture of nano titanium dioxide and chitosan; and the shell layer II is polylactic acid.
Citation Information
Patent Citations
Degradable film and preparation and application thereof
CN113136069A
Cited By
Ultra-high molecular weight polyethylene colored fiber as well as preparation method and application thereof
CN121087636A